Al Fikr Al Balaghi Fi Al Ma’ăni ‘Inda As Sakăki Fi Kitabihi Miftahul Ulum Dirăsah Balaghiyyah - Talqis Nurdianto (Jurnal Alsinatuna, 2017)
Miftāhul ‘Ulūm, written by al-Sakākī, especially the third part, was the beginning of a new phase in the development of Arabic rhetoric. Al-Sakākī divided the rhetoric into three fields of study, which are (1) Ma’ānī, (2) Bayān, (3) Badī’. However, his style is influenced by philosophers, theologians and their verbal lexicon, which are difficult to take, especially for the ordinary recipient. Al-Sakākī described that his book containing several types of literature, namely, ‘ilm ṣarf in complete version and its conclusion, derivation science, and the grammatical study in the completeness of Ma’ānī and Bayān. The meaning of Makna is the study of completeness and conclusion. Therefore, books and prose, and poem require al-‘Arūḍ and al-Qawāfī include Ṣarf, Grammar, Ma’ānī, Bayān, limitation, reasoning, al’Arūḍ, and al-Qawāfī. He argued that the fields of study were influential in delivering knowledge to the student in order to reach the goal of the author towards his book.This research was an analytical descriptive study of al-Sakākī rhetoric that focused on the normative aspect represented by rhetorical rule and aesthetic aspects. Those aspects were shown by the feeling. Al-Sakākī rhetoric thought is a method based on mental division and has conducted in the construction of many factors, which the most important of them are philosophy and logic. Keywords: thought, rhetoric, meanings, sakkaki, study